Propriedades eletrônicas de pontos quânticos contendo muitos elétrons - Melo, Heitor Alves de (2010)
This work investigates the electronic properties of semiconductor quantum dots in which there are many electrons confined. In particular, we study Si and Ge quantum dots embedded in dielectric matrices (SiO2 e HfO2). The theoretical method used to calculate the total energy of N electrons confined in quantum dots is based on a simplified version of the Hartree-Fock method. In this model, the total energy is obtained from single-particle wavefunctions and eigen-energies. The obtained results show that the total energy in Ge quantum dots are always larger than in Si ones. The reason is the smaller electron e effective mass in Ge, which raises the energies of the confined states. As for the role of the dielectric matrix, the total energy is always larger for SiO2 than for HfO2. Physically, this e effect is caused by the fact that SiO2 has larger confinement barriers (3.2 eV) than HfO2(1.5 eV). Smaller barriers favor larger spatial extent of the wavefunctions, decreasing the repulsion energy of the confined electrons. The chemical potential and additional energy was also calculated as function of the number of confined electrons. It was observed that the chemical potential of Ge quantum dots are always larger than Si ones, but the role of the dielectric matrix is inverted. The chemical potential for HfO2 is larger than for SiO2. With respect to the additional energy, we observed that this quantity strongly oscillates within the range 0 to 0.4 eV for cases. If one takes into account that the Coulomb blockade phenomena is only observed for additional energies much larger the thermal energy (of the order of 3/2kBT), this phenomena can only be observed for the case where there are only a few electrons confined in the quantum dots.